Prevalência de infecções hospitalares e assistência odontológica: um estudo transversal.: Infecções hospitalares e a saúde bucal - de Faria, Lara Maria Moreira; Douglas-de- Oliveira, Dhelfeson Willya; Silveira de Oliveira, Evandro; Ferreira de Aguiar, Elayne Cristina; Gomes de Fatima, Gessiane; Furtado Gonçalves, Patrícia; Dumont Flecha , Olga (Revista Estomatología, 2022)
Aim: To make a comparison between the prevalence of hospital infections over a period of 13 months between two groups: patients hospitalized without dental care and with dental care. Methods: This was a descriptive cross-sectional study, through data regarding the rates of hospital infections obtained in two groups: with and without dental care, considering more specifically the sectors: Intensive care unit (ICU) and neruological clinic. Patients over 16 years-old, of both genders and who were diagnosed with hospital infection after 48 hours of hospitalization or 48 hours after discharge, were included in the sample. Results: Between March 2016 and March 2017, a prevalence of hospital infection was observed of 3. 14% in patients without dental care and from March 2017 to March 2018, the prevalence was 2. 85% in patients who had dental care. Conclusion: The ICU was the sector with the highest occurrence of infections. Dental care was not associated with the occurrence of infections.